Automated control of fraction of inspired oxygen: is it time for widespread adoption?. Issue 2 (29th April 2021) - Mitra, Souvik; McMillan, Douglas
Abstract : Purpose of review: Over the past two decades, numerous algorithms for automated control of the fraction of inspired oxygen (FiO2 ) have been developed and incorporated into contemporary neonatal ventilators and high-flow devices in an attempt to optimize supplemental oxygen therapy in preterm infants. This review explores whether current evidence is sufficient to recommend widespread adoption of automated oxygen control in neonatal care. Recent findings: To date, 15 studies have compared automated versus manual control of FiO2 in preterm infants on respiratory support. This includes four new randomized cross-over trials published in the last 2 years. Available evidence consistently demonstrates a significant improvement in time spent within the target saturation range with automated FiO2 control. There are fewer episodes of severe hypoxemia and fewer manual FiO2 adjustments with automated oxygen control. Nursing workload may be reduced. However, no currently completed studies report on clinical outcomes, such as chronic lung disease or retinopathy of prematurity. Summary: Automated oxygen control appears to be a reasonable option for FiO2 titration in preterm infants on respiratory support, if resources are available, and might substantially reduce nursing workload. Further randomized clinical trials to explore its effects on clinical outcomes are required.